Medical Record Folder Design at Mazaya Clinic Pulung District, Ponorogo Regency - Mohammad Ardhi Fajar Setiawan; Rumpiati Rumpiati (program studi Rekam Medis dan Infomasi Kesehatan ITSK RS dr Soepraoen Malang, 2025)
Medical records are a critical element in health services at the Mazaya Clinic. Field observations revealed that the clinic does not yet have a medical record folder; Patient documents are only stapled sheets without classification or physical protection. This condition poses risks of document damage, data loss, privacy violations, and operational inefficiency, with search times reaching 12 minutes—far from the standards of the Ministry of Health Regulation No. 24/2022. This study aims to design an integrated medical record folder by optimizing three aspects: (1) anatomical structure, (2) physical material, and (3) content completeness.This research used the Borg & Gall Research and Development (R&D) model through four stages: Define, Design, Development, and Dissemination. The prototype was made using 310 gsm art carton laminated with matte finishing. The design was validated by experts and evaluated through field testing at the clinic. The results showed the folder increased document protection (80% moisture resistance), reduced search time by 75% (from 12 to 3 minutes), and improved data accuracy by reducing input errors by 25%. The study concludes that this folder design is a practical solution for supporting clinical accreditation, patient safety, and cost efficiency. Recommendations include technical training for staff, digital system synchronization, and data backup strategies.